Assertive skills program for social interaction in patients with anorexia and bulimia nervosa from a specialized clinic in Lima - Pacheco Ponce, Diana Marizol (2022)
This study had as aims to evaluate the effect of the assertive skills program for social interaction in a sample of patients with anorexia nervosa (AN) or bulimia nervosa (BN) who attended a specialized clinic in Lima. For these purposes, the research was carried out with a design of pre and posttest, in a group of 49 patients diagnosed with eating disorder, AN and BN symptoms, divided into experimental group (n = 24) and control group (n = 25). The Gismero´s Social Skills Scale (EHS), was used as an instrument to measure the dependent variable. After the intervention, the results shown statistically significant differences (p <.05 and p <.01) between the groups in general assertive skills, as well as in their different factors, except for the Factor I (self-expression in social situations) and the Factor V (making requests). It is concluded in the effectiveness of this program to increase certain assertive skills in this population.